Plant growth-promoting bacteria as biological control agents for sustainable agriculture: targeting root-knot nematodes - Mata, Adriana S.; Cruz, Carlos; Gaspar, João Rodrigues; Abrantes, Isabel; Conceição, Isabel Luci; Morais, Paula V.; Proença, Diogo Neves (Frontiers in Plant Science, 2025)
The increasing frequency of extreme weather events affects ecosystems and threatens food production. The reduction of chemical pesticides, together with other ecological approaches, is crucial to more sustainable agriculture. Plant-parasitic nematodes (PPN), especially root-knot nematodes (RKN), Meloidogyne spp., are responsible for extensive damage to a wide range of economically important crops, leading to yield losses and reduced quality of the products. This study aims to show the potential of native potato-growing soil bacterial strains as biological control agents in a more sustainable agriculture perspective. After screening thirty bacterial strains, a bacterial consortium, composed of B. amyloliquefaciens UC_2.4, P. capeferrum UC_21.3 A.1, and P. capeferrum UC_21.30 A.1, was defined and investigated in more detail due to their potential for plant growth-promoting bacteria (PGPB), fungicidal, and nematicidal activities. The genomes of the strains were sequenced and analyzed for PGPB traits, and phenotypic assays were also performed. The nematicidal activity of these strains towards PPN and the model organism Caenorhabditis elegans was assessed. Their potential as PGPB and for controlling PPN on soil was evaluated in pot assays with tomato plants cv. Coração de Boi, by using bacterial strains alone and as a consortium. Here, the bacterial consortium showed some PGPB traits verified by genome mining and phenotypic assays in vitro and pot assays with plants. It was able to act as nematicidal agents with 100% efficacy towards PPN but not against C. elegans, indicating a highly targeted action mechanism, which might be attributed to the surfactin, fengycin, and lipopeptides, not affecting other non-target organisms that play essential roles in soil health. The bacterial consortium reduced the infectivity of PPN in plants by threefold. This bacterial consortium was established for the first time and has the potential to serve as a new tool for managing RKN in a more sustainable agricultural environment.